Minat Belajar Matematika pada Siswa SMP Negeri 7 Padangsidimpuan - Nur Fauziah Siregar (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2020)
This study aims to determine the condition of class VII students' interest in learning mathematics at SMP Negeri 7 Padangsidimpuan. This research was conducted using a survey method. The population in this study were all students of class VII. As for the sample in this study were 26 students who were taken from the population with a sampling technique in accordance with the proportions. The instrument used was a learning interest questionnaire. Interest in learning questionnaires distributed to a sample of 20 items. The questionnaire that is distributed to the sample is a valid questionnaire. The results of this study indicate that the seventh grade students of SMP Negeri 7 Padangsidimpuan have moderate learning interest in mathematics.